A comparative study of effect of fluoroquinolones on blood glucose levels in rats - Gupta, Tanya; Mulkalwar, Sarita; Kulkarni, Vishwanath; Jadhav, Sudhir; Tilak, Abhijeet; Rane, Bhalchandra (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Fluoroquinolones (FQ) are frequently prescribed because of their broad-spectrum applicability in treatment of community acquired pneumonia and urinary tract infections. Increased use has raised some concerns regarding side effects like dysglycaemia, tendon rupture and QT interval prolongation. Gatifloxacin was banned in India in 2011 for causing fatal hypoglycemia. This study compares the effect of different fluoroquinolones on blood glucose levels in rats. Methods: 24 rats were divided into four study groups. Each group was administered one fluoroquinolone namely levofloxacin 9 mg, moxifloxacin 7.2 mg, ciprofloxacin 18 mg and ofloxacin 14.4 mg respectively for five days. The changes in blood glucose levels were observed for 10 days. Results: The mean blood glucose levels in all the four groups dropped below the baseline by day five. A statistically significant reduction in mean glucose levels was found in the moxifloxacin, ciprofloxacin and levofloxacin group. Among the rats that were given ofloxacin, the reduction in the mean blood glucose levels was not statistically significant. After stopping the drugs, the blood glucose levels in all the four groups returned near to the baseline within five days. Conclusions: The use of fluoroquinolones causes hypoglycemia in rats. The blood glucose level reduction associated with moxifloxacin was maximum, whereas ofloxacin appeared to have the minimum effect on blood glucose levels. These effects do not appear to be permanent and the dysglycaemia subsided after the drugs were stopped.